Indenture, Wayne County, 1895 - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1895)
Indenture, Wayne County, 1895. Official record on typewritten form with handwritten details for land bid in Wayne County, Georgia. March 5, 1895. From Wm. Scott to George Wilson. Includes tax receipt. 4 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Trust indentures; Wayne County (Ga.); Court records; Records and correspondence